ENGLISH TECHING MANAGEMENT IN SENIOR HINGH SCHOOL - Faujia Umasugi (JURNAL DODOTO, 2021)
To prepare quality human resources and have good communicative skills in English as an international language and the attention and interest of the community is very high on the importance of mastering English, the government and the community respond by making learning English as one of the competencies mastered by participants. English language competence is achieved both orally and in writing. Such English learning can be realized if all aspects of learning management, namely: learning objectives, syllabus, and teacher roles must be fulfilled properly. Setting methods, strategies, and equipment in learning is part of learning management activities that must be carried out by teachers. Learning management is an effort to manage learning which includes planning, implementation, and evaluation of learning as well as supervision in order to achieve learning objectives effectively and efficiently. Students have been provided by teachers with the ability to speak in various types of dialogue for various purposes, both formally and informally, and this means that teachers and students have carried out learning to speak as an activity of getting and using skills. Through the two activities mentioned above, the nature of language learning objectives has been fulfilled which not only includes competence but also language performance which is actually complex.